Revitalizing Interior Designs in Religious Shrines: رؤى صلاح الدين حامد فريد-فاتن عباس الاسدي (Al-Academy, 2019)
The current research is interested in the objective study of revitalizing the religious sites and the extent to which they achieve the pragmatic and semantic ends, because they are derived from history and civilization and have a clear impact over the recipient. The research question is (what are the techniques of developing the spaces of the religious shrines in accordance with revitalizing the interior spaces within them?). The research aims at determining the weak and strong points in the process of revitalizing the interior spaces in the religious shrines. The theoretical framework consists of two parts: the first addressed the revitalization in the interior design, and the second addressed the religious shrines and their influence in the interior design. The current research procedures utilized the descriptive approach. The research studied the religious shrines that witness revitalization within the new construction in the holy shrines of Imam Hussein and Imam Abbas in addition to choosing (the space of the dome) for the study. The results of the study show that the organization of the roofing of the spaces in the two samples came to ensure the functional and decorative sides in new ways and has been away from the historical organization represented by the originality of the space